The COVID‐19 pandemic and youth with anorexia nervosa: A retrospective comparative cohort design. Issue 1 (20th September 2022) - Datta, Nandini; Van Wye, Eliza; Citron, Kyra; Matheson, Brittany; Lock, James D.
Abstract: Objective: There is a growing body of literature suggesting the novel coronavirus pandemic (COVID‐19) negatively impacts mental health in individuals self‐reporting an eating disorder (ED); however, limited pediatric data is available about the impact COVID‐19 has had on youth with EDs, specifically Anorexia Nervosa (AN). Our study uses a cross‐sectional design to explore differences in ED symptoms between adolescents diagnosed with AN during the COVID‐19 pandemic compared to a retrospective cohort of adolescents for whom these measures were previously collected, prior to the pandemic. Method: We report cross‐sectional data assessing differences between AN behaviors and cognitions during the COVID‐19 pandemic compared to a retrospective cohort ( n  = 25 per cohort) assessed before the pandemic. Results: Results suggest that individuals with a first‐time diagnosis of AN during the pandemic had lower percent expected body weight, and more compulsive exercise behaviors. Conclusions: These data support existing pediatric findings in exercise and body weight differences in adolescents with AN before and during the pandemic. Findings may be helpful in informing considerations for providers treating ED patients amidst and after the pandemic. Public Significance: This manuscript compares a retrospective cohort of adolescents diagnosed with AN prior to the pandemic to a cohort of adolescents diagnosed with AN during the pandemic. Results report that adolescents diagnosed with AN during the pandemic have lower weights and increased compensatory exercise behavior compared to adolescents diagnosed with AN before the pandemic despite no difference in length of illness. Findings may be helpful in informing considerations for providers treating ED patients amidst and after the pandemic.